2017
DOI: 10.1016/j.bpj.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

GsMTx4: Mechanism of Inhibiting Mechanosensitive Ion Channels

Abstract: GsMTx4 is a spider venom peptide that inhibits cationic mechanosensitive channels (MSCs). It has six lysine residues that have been proposed to affect membrane binding. We synthesized six analogs with single lysine-to-glutamate substitutions and tested them against Piezo1 channels in outside-out patches and independently measured lipid binding. Four analogs had ∼20% lower efficacy than the wild-type (WT) peptide. The equilibrium constants calculated from the rates of inhibition and washout did not correlate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 69 publications
4
141
1
Order By: Relevance
“…And the recent crystal structure of TRAAK [46] supports a model where inner monolayer tension gates K2P channels. Our tests with GsMTx4 also support this model, as GsMTx4 potentiates TREK1 MSC currents when applied to outside-out patches suggesting peptide relief of outer monolayer tension increases tension on the inner monolayer [74]. This may be due to a combination of GsMTx4 inducing negative curvature in the resting patches and/or acting as an outer monolayer tension clamp when pressure is applied.…”
Section: Gsmtx4 Mechanism Of Inhibition and Modulation Of Piezo Vs K+supporting
confidence: 62%
See 1 more Smart Citation
“…And the recent crystal structure of TRAAK [46] supports a model where inner monolayer tension gates K2P channels. Our tests with GsMTx4 also support this model, as GsMTx4 potentiates TREK1 MSC currents when applied to outside-out patches suggesting peptide relief of outer monolayer tension increases tension on the inner monolayer [74]. This may be due to a combination of GsMTx4 inducing negative curvature in the resting patches and/or acting as an outer monolayer tension clamp when pressure is applied.…”
Section: Gsmtx4 Mechanism Of Inhibition and Modulation Of Piezo Vs K+supporting
confidence: 62%
“…To better understand GsMTx4’s effects on membranes we synthesized six lysine-glutamate peptide analogs and tested them against Piezo1 channels in patches [74]. We found several analogs with compromised inhibitory activity.…”
Section: Gsmtx4 Mechanism Of Inhibition and Modulation Of Piezo Vs K+mentioning
confidence: 99%
“…To further test the potential link between lipid domains and calcium exchange kinetics upon RBC deformation, we used the peptide GsMTx4, a validated inhibitor of the mechanoactivated ion channels [37] which are mostly responsible for the calcium entry upon RBC deformation [1]. We showed that this treatment abolished calcium entry as well as GM1-and SM-enriched domain increase without inducing detectable toxicity (Suppl.…”
Section: Conrard Et Al: Three Lipid Domains At the Erythrocyte Surfacementioning
confidence: 99%
“…The free energy profiles from the all‐atom and CG simulations for the wild‐type peptide were within 6 kJ mol −1 . The Δ G b predicted from the CG simulations ranged from −18 kJ mol −1 to −27 kJ mol −1 while the corresponding values reported from Trp quenching experiments were −25 kJ mol −1 to −26 kJ mol −1 . The ΔΔ G b for the K‐E mutants predicted from simulations ranged from −2 kJ mol −1 to 4 kJ mol −1 while the ΔΔ G b from experiments was <1 kJ mol −1 for all mutants.…”
Section: Membrane Binding Of Disulfide‐rich Peptides Targeting Voltagmentioning
confidence: 79%
“…Nishizawa et al used both all‐atom and CG simulations to calculate the free energy for the binding of GsMTx4 and analogues thereof to a POPC membrane. The aim was to investigate the relationship between membrane binding properties of the peptide and activity on the MSC Piezo1 . For this, the simulations studied the effect of K to E mutations on the insertion depths and orientation of the peptide in the membrane and their binding affinities.…”
Section: Membrane Binding Of Disulfide‐rich Peptides Targeting Voltagmentioning
confidence: 99%